Potency of Industrial Tea Waste: Comparison Between Green And Black Tea Industrial Wastes as UV Filter for Sunscreen - Martono, Yohanes (Indonesian Research Gateway, 2010)
Indonesia is one of ten biggest countries that produce tea for world. It makes Indonesia produce various tea products. Every tea production process produces the large quantity of industrial tea wastes every day. Our previous research showed that industrial tea wastes still have antioxidant activity. It means that industrial tea wastes contained of phenolic compounds which can be used as UV filter for sunscreen. This research compared antioxidant activity, total phenolic contents and UV filter effectivenessÃÂ between green and black industrial tea wastes. Antioxidant activity were analyzed by reducing power and DPPHÃÂ method, total phenolic contents of tea wastes extract were analyzedÃÂ using Folin-Ciocalteu assay, while UV filter effectiveness were assessed by UV spectra and absorbance of each tea wastes extract related to its concentration in order to yield maximum protection. The results showed that although green tea waste extract had higher antioxidant activity but adversely, black tea had higher total phenolic contents. UV filter effectiveness is affected by polyphenols content in substances, so it suggested that black tea waste extract is more potential than green tea waste extract as photoprotection substance.